Preparation method and application of PAIN deposited high-valence lithium ion sieve composite graphene oxide loaded carbon cloth
By loading the LMO composite GO to the EACC, and using anode oxidation method and ESIX technology to solve the problem of the problem of powder traits and low lithium lifting efficiency of lithium ion sieve in the aqueous solution, the efficient and environmentally friendly lithium ion sieve system is available. application.
Patent Information
- Application Number
- CN202411694306.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-28
AI Technical Summary
The powder properties of existing lithium ion sieves in aqueous solutions limit their development, and the lithium extraction method that is directly in contact with the lithium-containing solution is less efficient.
High -priced lithium ionic sieve compound glycehene load carbon fabrics with Pain deployed. By loading LMO composite GO to EACC, and using anode oxidation method to increase the MN price, combined with electrochemical ion switch technology (ESIX) to increase lithium The adsorption rate and structural stability of ions.
Realize low MN -dissolved damage, high electrical and high -absorbing rates. There is no need to pick up during the solution process, saving the use of chemicals, and improving the efficiency and environmental protection of lithium lifting.
Smart Images

Figure CN119370843A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a lithium ion sieve. Background Art
[0002] With the rapid development of electric vehicles, people's demand for lithium resources has increased dramatically. As a result, global lithium prices have risen sharply in the past five years, and the development of lithium resources has become increasingly important. Lithium is mainly distributed in ores, salt lake brine and seawater. Among them, the lithium content in salt lake brine accounts for two-thirds. Therefore, mining lithium from salt lake brine and seawater is a good alternative to solve the problem of lithium shortage. In recent years, there have been many research methods for extracting lithium from seawater and brine, such as precipitation, calcination leaching, solvent extraction and adsorption. Among the many methods that have been studied, the adsorption method has the advantages of high efficiency, simplicity, and green environmental protection. However, these methods are all direct extraction and have low efficiency. Therefore, it is urgent to develop an adsorbent combined with a new lithium extraction method to meet the challenges of future lithium resource supply.
[0003] Lithium manganese oxide ion sieves (LMO) are promising candidates for applications in the manufacture of lithium manganese oxides due to their low toxicity, low cost, high chemical stability and large Li absorption capacity. + It is widely considered to be one of the most promising adsorbents due to its ability to absorb lithium. However, its powdery properties in aqueous solution limit its development. In addition, the conventional lithium ion extraction process is in direct contact with the lithium-containing solution, which is inefficient. Summary of the invention
[0004] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a preparation method and application of a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth.
[0005] The present invention proposes to load LMO composite GO after acid washing onto EACC as an electrode and ESIX; the addition of GO makes LMO more stable, reduces the change of LMO during charging and discharging, and reduces the peeling of powder; and the large specific surface area and rich pore structure are conducive to the rapid transmission and diffusion of lithium ions; and the loading of EACC further increases the reaction contact area; and the valence state of Mn is increased by anodization method, further improving the stability of the lithium ion sieve structure; finally, due to the application of ESIX, the lithium ions in the solution are accelerated to move to the lithium ion sieve, thereby increasing the adsorption rate; no acid washing is required during desorption, only reverse power supply is required. It greatly saves the use of chemicals, contributes to environmental protection, and provides guidance for green lithium extraction.
[0006] The present invention develops a lithium ion sieve of polyaniline composite graphene oxide loaded carbon cloth with low Mn dissolution loss, high conductivity, high adsorption rate and no need for acid washing during desorption; the method comprises the following steps:
[0007] A method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth is specifically completed by the following steps:
[0008] 1. Activation of carbon cloth:
[0009] ①, washing the carbon cloth, and then drying it to obtain the cleaned carbon cloth;
[0010] ②. Clamp the cleaned carbon cloth in the electrode holder as the working electrode, use the platinum sheet as the counter electrode, immerse the working electrode and the counter electrode in HNO3 / H2SO4 acid solution, perform electrochemical activation for a period of time at a constant potential, take out and rinse with distilled water to obtain the activated carbon cloth;
[0011] 2. Preparation of HMO@GO:
[0012] ①, dispersing graphene oxide in deionized water and ultrasonically treating for a period of time to obtain a graphene oxide dispersion;
[0013] ②, MnCl2·4H2O, LiOH·H2O and H2O2 solutions were added into deionized water and ultrasonicated for a period of time to obtain mixed solution Ⅰ;
[0014] ③, mixing the graphene oxide dispersion and the mixed solution I uniformly to obtain a mixed solution II;
[0015] ④, the mixed solution II is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and then hydrothermally reacted at 160°C to 180°C for a period of time to obtain a reaction product; the reaction product is washed, then dried, and then washed in HCl solution or sulfuric acid solution for a period of time, then filtered, and then dried to obtain HMO@GO;
[0016] 3. Preparation of HMO@GO / EACC:
[0017] ①, PVDF powder or polyvinyl pyrrolidone and HMO@GO are mixed evenly to obtain a mixed powder; the mixed powder is added to dimethylacetamide, and ultrasonically dispersed for 20min to 30min to obtain a lithium ion sieve slurry; the lithium ion sieve slurry is evenly coated on the surface of the cleaned carbon cloth, and then placed in a vacuum drying oven for drying;
[0018] ②, repeat step 3① 4 to 6 times to obtain HMO@GO / EACC;
[0019] 4. Preparation of high-priced HMO@GO / EACC:
[0020] Using HMO@GO / EACC as the positive electrode, platinum sheet as the negative electrode, and 0.5 mol / L H2SO4 solution as the electrolyte, electrolysis was performed at a voltage of 10V to 20V for a period of time to obtain high-valent HMO@GO / EACC;
[0021] 5. Deposition of PANI on high-priced HMO@GO / EACC:
[0022] The high-priced HMO@GO / EACC was cleaned with anhydrous ethanol, and the cleaned high-priced HMO@GO / EACC was used as the positive electrode, the platinum sheet was used as the negative electrode, and a mixed solution of aniline and H2SO4 was used as the electrolyte. Deposition was performed at 1V to 2V for a period of time. After the deposition was completed, the carbon cloth was taken out, cleaned, and dried to obtain the high-priced HMO@GO / EACC deposited with polyaniline, that is, the high-priced lithium ion sieve composite graphene oxide loaded carbon cloth deposited with PAIN.
[0023] A PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth is used for electrically controlled lithium extraction.
[0024] Principle of the present invention:
[0025] Electrochemical ion switch technology (ESIX) is based on the principle of electrochemical reaction. By applying voltage or current, ions are induced to move between electrolyte solution and electrode material. The lithium extraction efficiency can be greatly increased by combining manganese lithium ion sieve and electrochemical ion switch technology. Therefore, the preparation of a new manganese lithium ion sieve for ESIX has become a hot topic in industry research. The valence state of Mn in manganese lithium ion sieve prepared by ordinary methods is difficult to reach tetravalence, and the anodic oxidation method can increase the valence state of lithium ion sieve. And because the lithium ion sieve itself usually has a low conductivity, by loading it on graphene oxide (GO), its electron transmission ability can be improved and the electrochemical performance can be improved. In addition, GO Good mechanical strength and flexibility can provide a solid substrate and improve the structural stability of the lithium ion sieve; it can also reduce the volume change of the lithium ion sieve during the charge and discharge process, reduce the pulverization and peeling of the material, and improve the cycle stability; the present invention loads LMO composite GO after acid washing (HMO / GO) onto the activated CC (EACC), and then uses the anodic oxidation method to increase the valence state of Mn and increase the stability of the lithium ion sieve; by using HMO@GO / EACC as the electrode in ESIX, not only can the contact area between the lithium ion sieve and the lithium-containing solution be increased, but also the speed of lithium extraction can be increased due to the action of the current, and the traditional method of using acid to desorb the lithium ion sieve is avoided. This greatly increases the efficiency of lithium extraction and saves energy, thereby achieving efficient lithium extraction.
[0026] Advantages of the present invention:
[0027] Compared with the traditional lithium ion sieve, the lithium ion sieve composite GO loaded on EACC obtains conductivity and increases the reaction area, and can be used as an electrode to participate in the electrochemical ion switch technology. Through the anodic oxidation method, the valence state of Mn is made closer to +4, and the stability of the lithium ion sieve structure is further increased, which is higher than the ordinary lithium ion sieve preparation method. In addition, due to the power-on, the adsorption rate of lithium ions moving to the cathode is increased; the adsorption amount reaches 34.6 mg / g, and the adsorption time is 20 min, which is better than the traditional lithium ion sieve; the high-valent HMO@GO / EACC has great application potential in the field of lithium ion screening and lithium extraction. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a preparation mechanism diagram of a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth of the present invention;
[0029] Figure 2 The adsorption capacity of the high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth deposited by PAIN prepared in Example 1;
[0030] Figure 3 The selective adsorption performance of the high-valent lithium ion sieve composite graphene oxide-supported carbon cloth deposited by PAIN prepared in Example 1;
[0031] Figure 4 The cycle performance of the high-valent lithium ion sieve composite graphene oxide supported carbon cloth adsorbing lithium ions deposited by PAIN prepared in Example 1;
[0032] Figure 5 The graphs show the adsorption capacity of lithium ions and the Mn dissolution rate of the high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth deposited by PAIN prepared in Examples 1 to 5. DETAILED DESCRIPTION
[0033] Specific implementation method 1: This implementation method is a method for preparing a high-valent lithium ion sieve composite graphene oxide loaded carbon cloth deposited by PAIN, which is specifically completed according to the following steps:
[0034] 1. Activation of carbon cloth:
[0035] ①, washing the carbon cloth, and then drying it to obtain the cleaned carbon cloth;
[0036] ②. Clamp the cleaned carbon cloth in the electrode holder as the working electrode, use the platinum sheet as the counter electrode, immerse the working electrode and the counter electrode in HNO3 / H2SO4 acid solution, perform electrochemical activation for a period of time at a constant potential, take out and rinse with distilled water to obtain the activated carbon cloth;
[0037] 2. Preparation of HMO@GO:
[0038] ①, dispersing graphene oxide in deionized water and ultrasonically treating for a period of time to obtain a graphene oxide dispersion;
[0039] ②, MnCl2·4H2O, LiOH·H2O and H2O2 solutions were added into deionized water and ultrasonicated for a period of time to obtain mixed solution Ⅰ;
[0040] ③, mixing the graphene oxide dispersion and the mixed solution I uniformly to obtain a mixed solution II;
[0041] ④, the mixed solution II is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and then hydrothermally reacted at 160°C to 180°C for a period of time to obtain a reaction product; the reaction product is washed, then dried, and then washed in HCl solution or sulfuric acid solution for a period of time, then filtered, and then dried to obtain HMO@GO;
[0042] 3. Preparation of HMO@GO / EACC:
[0043] ①, PVDF powder or polyvinyl pyrrolidone and HMO@GO are mixed evenly to obtain a mixed powder; the mixed powder is added to dimethylacetamide, and ultrasonically dispersed for 20min to 30min to obtain a lithium ion sieve slurry; the lithium ion sieve slurry is evenly coated on the surface of the cleaned carbon cloth, and then placed in a vacuum drying oven for drying;
[0044] ②, repeat step 3① 4 to 6 times to obtain HMO@GO / EACC;
[0045] 4. Preparation of high-priced HMO@GO / EACC:
[0046] Using HMO@GO / EACC as the positive electrode, platinum sheet as the negative electrode, and 0.5 mol / L H2SO4 solution as the electrolyte, electrolysis was performed at a voltage of 10V to 20V for a period of time to obtain high-valent HMO@GO / EACC;
[0047] 5. Deposition of PANI on high-priced HMO@GO / EACC:
[0048] The high-priced HMO@GO / EACC was cleaned with anhydrous ethanol, and the cleaned high-priced HMO@GO / EACC was used as the positive electrode, the platinum sheet was used as the negative electrode, and a mixed solution of aniline and H2SO4 was used as the electrolyte. Deposition was performed at 1V to 2V for a period of time. After the deposition was completed, the carbon cloth was taken out, cleaned, and dried to obtain the high-priced HMO@GO / EACC deposited with polyaniline, that is, the high-priced lithium ion sieve composite graphene oxide loaded carbon cloth deposited with PAIN.
[0049] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that in step 1①, the carbon cloth is washed 2 to 4 times with anhydrous ethanol, acetone and distilled water respectively, and then dried at room temperature; the size of the carbon cloth described in step 1① is (1 cm to 2 cm) × (2 cm to 3 cm). The other steps are the same as those in specific implementation method 1.
[0050] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the HNO3 / H2SO4 acid solution described in step 1② is a mixture of HNO3 with a mass fraction of 65% and H2SO4 with a mass fraction of 98% in a volume ratio of 1:1; the constant potential described in step 1② is 4V to 6V; the time of electrochemical activation described in step 1② is 10min to 20min. The other steps are the same as those in specific implementation method 1 or 2.
[0051] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the ultrasonic treatment time in step 2① is 20 min to 30 min; the mass fraction of the graphene oxide dispersion in step 2① is 0.5% to 1%. The other steps are the same as those in specific embodiments 1 to 3.
[0052] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the mass volume ratio of MnCl2·4H2O, LiOH·H2O, H2O2 solution and deionized water described in step 2② is (3g~5g):(2g~4g):(2mL~4mL):50mL; the mass fraction of H2O2 solution described in step 2② is 25%~35%; the time of ultrasonic treatment described in step 2② is 1h~2h; the volume ratio of graphene oxide dispersion and mixed solution I described in step 2③ is (50mL~100mL):50mL. The other steps are the same as those of specific embodiments 1 to 4.
[0053] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the time of the hydrothermal reaction described in step 2 ④ is 8h to 12h; in step 2 ④, the reaction product is washed 3 to 5 times with deionized water, then dried at 60°C, and then washed in a 1mol / L HCl solution or a 0.5mol / L sulfuric acid solution for 6h to 10h, filtered, and then dried at 60°C to obtain HMO@GO. The other steps are the same as those of specific embodiments 1 to 5.
[0054] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that: the mass ratio of the mixed powder in the lithium ion sieve slurry described in step 3① to the volume ratio of dimethylacetamide is 1g:(45mL~50mL); the mass ratio of the PVDF powder or polyvinyl pyrrolidone and HMO@GO described in step 3① is (0.1~0.2):(0.8~0.9); the volume ratio of the lithium ion sieve slurry described in step 3① to the surface area of the carbon cloth is (1mL~5mL):(0.8cm 2 ~1cm 2 ); the vacuum drying temperature in step 3① is 60°C to 80°C, and the vacuum drying time is 1h to 2h. The other steps are the same as those in specific embodiments 1 to 6.
[0055] Specific embodiment eight: The difference between this embodiment and specific embodiments one to seven is that: the electrolysis time described in step four is 0.5h~1h; the high-priced HMO@GO / EACC is cleaned 1 to 3 times with anhydrous ethanol described in step five; the mixed solution of aniline and H2SO4 described in step five is a mixed solution of aniline, H2SO4 and water, wherein the concentration of aniline is 0.5mol / L~0.15mol / L, and the concentration of H2SO4 is 0.5mol / L~0.15mol / L; the deposition time at 1V~2V in step five is 20min~40min; after the deposition in step five is completed, the carbon cloth is taken out, cleaned 1 to 4 times with anhydrous ethanol, and then dried at 60℃~80℃. The other steps are the same as specific embodiments one to seven.
[0056] Specific embodiment 9: This embodiment is a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth for electrically controlled lithium extraction.
[0057] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth is used for electrically controlled lithium extraction, which is specifically completed in the following steps:
[0058] The PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth is used as a cathode, a platinum sheet is used as an anode, and a lithium-containing solution is used as an electrolyte, and electrolysis is performed at a voltage of 5V to 7V for 20min to 30min to obtain the PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth that adsorbs lithium. The other steps are the same as those in the first to ninth embodiments.
[0059] The following examples are used to verify the beneficial effects of the present invention:
[0060] Example 1: A method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth, which is specifically completed by the following steps:
[0061] 1. Activation of carbon cloth:
[0062] ①, wash the carbon cloth with a size of 1 cm × 2.5 cm twice with anhydrous ethanol, acetone and distilled water respectively, and then dry it at room temperature to obtain the cleaned carbon cloth;
[0063] ②. Clamp the cleaned carbon cloth (size 1cm×1cm) in the electrode holder as the working electrode, and use the platinum sheet as the counter electrode. Immerse the working electrode and the counter electrode in HNO3 / H2SO4 acid solution, and perform electrochemical activation at a constant potential of 6V for 10min. After taking out, rinse with distilled water to obtain the activated carbon cloth (EACC);
[0064] The HNO3 / H2SO4 acid solution described in step 1② is a mixture of 65% HNO3 by mass and 98% H2SO4 by mass in a volume ratio of 1:1;
[0065] 2. Preparation of HMO@GO:
[0066] ①, dispersing graphene oxide in deionized water and ultrasonically treating for 20 minutes to obtain a graphene oxide dispersion;
[0067] The mass fraction of the graphene oxide dispersion described in step 2① is 0.5%;
[0068] ②, 3.958g MnCl2·4H2O, 2.5176g LiOH·H2O and 2.5mL H2O2 solution were added into 50mL deionized water and ultrasonicated for 2h to obtain mixed solution Ⅰ;
[0069] The mass fraction of the H2O2 solution described in step 2② is 30%;
[0070] ③, mixing the graphene oxide dispersion and the mixed solution I uniformly to obtain a mixed solution II;
[0071] The volume ratio of the graphene oxide dispersion described in step 2③ to the mixed solution I is 100mL:50mL;
[0072] ④. Transfer the mixed solution II to a stainless steel autoclave lined with polytetrafluoroethylene, and then perform a hydrothermal reaction at 170°C for 10 hours to obtain a reaction product; wash the reaction product with deionized water for 3 times, then dry it at 60°C, then enter 1 mol / L HCl solution for washing for 8 hours, then filter it, and then dry it at 60°C to obtain HMO@GO;
[0073] 3. Preparation of HMO@GO / EACC:
[0074] ①, 0.1g PVDF powder and 0.9g HMO@GO were mixed evenly to obtain a mixed powder; the mixed powder was added to DMF and ultrasonically dispersed for 30min to obtain a lithium ion sieve slurry; the lithium ion sieve slurry was evenly coated on the surface of the cleaned carbon cloth, and then placed in a vacuum drying oven at a temperature of 60°C and dried for 1h;
[0075] The mass ratio of the mixed powder in the lithium ion sieve slurry described in step 3① to the volume ratio of DMA is 1g:45mL;
[0076] The ratio of the volume of the lithium ion sieve slurry described in step 3① to the surface area of the carbon cloth is 5mL:1cm 2 ;
[0077] ②, repeat step 3① 5 times to obtain HMO@GO / EACC;
[0078] 4. Preparation of high-priced HMO@GO / EACC:
[0079] Using HMO@GO / EACC as the positive electrode, platinum sheet as the negative electrode, and 0.5 mol / L H2SO4 solution as the electrolyte, electrolysis was performed at a voltage of 10 V for 1 h to obtain high-valent HMO@GO / EACC:
[0080] 5. Deposition of PANI on high-priced HMO@GO / EACC:
[0081] The high-priced HMO@GO / EACC was washed three times with anhydrous ethanol, and the washed high-priced HMO@GO / EACC was used as the positive electrode, the platinum sheet was used as the negative electrode, and the mixed solution of aniline and H2SO4 was used as the electrolyte, and the deposition was carried out at 1V for 30min. After the deposition was completed, the carbon cloth was taken out, washed three times with anhydrous ethanol, and then dried at 60°C to obtain the high-priced HMO@GO / EACC deposited with polyaniline, that is, the high-priced lithium ion sieve composite graphene oxide loaded carbon cloth deposited with PAIN;
[0082] The mixed solution of aniline and H2SO4 described in step 5 is a mixed solution of aniline, H2SO4 and water, wherein the concentration of aniline is 0.1 mol / L, and the concentration of H2SO4 is 0.1 mol / L.
[0083] Example 2: The difference between this example and Example 1 is that in step 3, 0.2 g of PVDF powder and 0.8 g of HMO@GO are mixed evenly to obtain a mixed powder. The other steps and parameters are the same as those in Example 1.
[0084] Example 3: The difference between this example and Example 1 is that in step 3, 0.1 g of polyvinyl pyrrolidone and 0.9 g of HMO@GO are mixed evenly to obtain a mixed powder. The other steps and parameters are the same as those in Example 1.
[0085] Example 4: This example is different from Example 1 in that in step 4, the electrolysis is performed at a voltage of 20 V for 0.5 h. The other steps and parameters are the same as those in Example 1.
[0086] Example 5: The difference between this example and Example 1 is that in step 3 ②, step 3 ① is repeated 3 times, and the other steps and parameters are the same as those in Example 1.
[0087] The high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth (HMO@GO / EACC) prepared in Example 1 was added to a 200 mg / L LiCl solution for adsorption for 30 min to 240 min. The Li content in the solution during the adsorption process was tested at different times. + The concentration of adsorption capacity is shown in Figure 2 As shown in the HMO@GO / EACC curve;
[0088] The high-valent lithium ion sieve composite graphene oxide supported carbon cloth (HMO
[0089] @GO / EACC) as the cathode, platinum sheet as the anode, 200 mg / L LiCl solution as the electrolyte, electrolysis at a voltage of 6 V for 30 min to 240 min, to obtain the high-valent lithium ion sieve composite graphene oxide loaded carbon cloth with PAIN deposition for adsorbing lithium. The Li in the solution during the adsorption process at different times was tested. + The concentration of adsorption capacity is shown in Figure 2 HMO@
[0090] The curve of GO / EACC voltage is shown;
[0091] Figure 2 The adsorption capacity of the high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth deposited by PAIN prepared in Example 1;
[0092] Figure 2 It can be seen that the adsorption rate of Li by HMO@GO / EACC without voltage is very slow, reaching equilibrium in about 4 hours. After voltage is applied, the adsorption rate is accelerated, and adsorption equilibrium can be reached in only 30 minutes, which greatly increases the efficiency of lithium extraction.
[0093] The high-valent lithium ion sieve composite graphene oxide supported carbon cloth (HMO
[0094] @GO / EACC) were placed in Li + Mg 2+ 、Na + , K +In the solution, the adsorption experiment was carried out for 6 hours without applying voltage to test the Li + Mg 2+ 、Na + , K + The concentration of , and thus the adsorption amount is calculated, the adsorption capacity is shown in Figure 3 As shown in the HMO@GO / EACC bar graph;
[0095] The high-valent lithium ion sieve composite graphene oxide supported carbon cloth (HMO
[0096] @GO / EACC) as the cathode, platinum as the anode, and Li + Mg 2+ 、Na + , K + The solution was used as the electrolyte and electrolyzed at a voltage of 0.6 V for 30 min. After the adsorption was completed, the Li + Mg 2+ 、Na + , K + The adsorption capacity can be calculated by the content of ions. Figure 3 As shown in the HMO@GO / EACC voltage bar graph;
[0097] Figure 3 The selective adsorption performance of the high-valent lithium ion sieve composite graphene oxide-supported carbon cloth deposited by PAIN prepared in Example 1;
[0098] like Figure 3 As shown, HMO@GO / EACC has a significant effect on Na + , K + and Mg 2+ The selectivity coefficients are 9.86, 13 and 5.2 respectively. After voltage is applied, the selectivity coefficients are 8.68, 10.17 and 4.83. This is mainly due to the fact that a large number of cations move to the cathode and are adsorbed by the lithium ion sieve.
[0099] The high-valent lithium ion sieve composite graphene oxide loaded carbon cloth (HMO@GO / EACC) prepared in Example 1 was used as the cathode, the platinum sheet was used as the anode, and the LiCl solution with a concentration of 200 mg / L was used as the electrolyte. The electrolyte was electrolyzed at a voltage of 0.6 V for 30 min. The Li in the solution after adsorption for 30 min was tested. + Concentration and Mn 2+ concentration, and thus calculate the Li + Adsorption amount and Mn 2+Then put it in deionized water for desorption, at this time, HMO@GO / EACC is used as anode, platinum sheet is used as cathode, and the voltage is 0.6V; then replace the LiCl solution with a concentration of 200mg / L as electrolyte, swap the anode and cathode, and conduct the adsorption experiment again; after the adsorption is completed, the Li + Concentration and Mn 2+ Concentration, cyclic adsorption and desorption ten times, get Figure 4 .
[0100] Figure 4 The cycle performance of the high-valent lithium ion sieve composite graphene oxide supported carbon cloth adsorbing lithium ions deposited by PAIN prepared in Example 1;
[0101] like Figure 4 As shown in the figure, after 10 cycles of adsorption, the adsorption amount did not show a significant decrease compared with the first time, and the adsorption amount could still reach 27.1 mg.g after the tenth desorption. -1 This is due to the fact that in the ESIX process, the adsorption and desorption of ions are achieved by adjusting the reduction and oxidation potential of the membrane. + The adsorption and desorption process will not cause damage to the lithium ion sieve, and the Mn dissolution loss is also very low, but traditional acid washing will cause the dissolution of the spinel structure.
[0102] The high-valent lithium ion sieve composite graphene oxide loaded carbon cloth (HMO@GO / EACC) prepared in Examples 1 to 5 was used as the cathode, the platinum sheet was used as the anode, and the LiCl solution with a concentration of 200 mg / L was used as the electrolyte. The electrolyte was electrolyzed at a voltage of 0.6 V for 30 min. The concentration of the solution at different adsorption times was tested to calculate the adsorption amount. Figure 5 As shown;
[0103] Figure 5 The graphs show the adsorption capacity of lithium ions and the Mn dissolution rate of the high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth deposited by PAIN prepared in Examples 1 to 5.
[0104] Figure 5 It can be seen that in Example 2, after 0.2g PVDF powder and 0.8g HMO@GO were mixed evenly, the adsorption amount became less, and the Mn dissolution loss was also reduced. The increase in the proportion of PVDF will reduce the adsorption amount and Mn dissolution loss. In Example 3, 0.1g PVDF was replaced with polyvinyl pyrrolidone and 0.9g HMO@GO were mixed evenly, and the adsorption amount and Mn dissolution loss did not change much. In Step 4 of Example 4, electrolysis was performed at a voltage of 20V for 0.5h. Excessive voltage will destroy the lithium ion sieve a little, causing the adsorption amount to decrease slightly. The reduction in electrolysis time may also cause Mn to not be completely oxidized, and the Mn dissolution loss will increase. In Step 3 of Example 5, coating and drying are performed 3 times so that less lithium ion sieve is loaded on the carbon cloth, so the adsorption amount is reduced.
Claims
1. A method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth, characterized in that The preparation method is specifically completed according to the following steps:
1. Activation of carbon cloth: ①, washing the carbon cloth, and then drying it to obtain the cleaned carbon cloth; ②. Clamp the cleaned carbon cloth in the electrode holder as the working electrode, use the platinum sheet as the counter electrode, immerse the working electrode and the counter electrode in HNO3 / H2SO4 acid solution, perform electrochemical activation for a period of time at a constant potential, take out and rinse with distilled water to obtain the activated carbon cloth; 2. Preparation of HMO@GO: ①, dispersing graphene oxide in deionized water and ultrasonically treating for a period of time to obtain a graphene oxide dispersion; ②, MnCl2·4H2O, LiOH·H2O and H2O2 solutions were added into deionized water and ultrasonicated for a period of time to obtain mixed solution Ⅰ; ③, mixing the graphene oxide dispersion and the mixed solution I uniformly to obtain a mixed solution II; ④, the mixed solution II is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and then hydrothermally reacted at 160°C to 180°C for a period of time to obtain a reaction product; the reaction product is washed, then dried, and then washed in HCl solution or sulfuric acid solution for a period of time, then filtered, and then dried to obtain HMO@GO; 3. Preparation of HMO@GO / EACC: ①, PVDF powder or polyvinyl pyrrolidone and HMO@GO are mixed evenly to obtain a mixed powder; the mixed powder is added to dimethylacetamide, and ultrasonically dispersed for 20min to 30min to obtain a lithium ion sieve slurry; the lithium ion sieve slurry is evenly coated on the surface of the cleaned carbon cloth, and then placed in a vacuum drying oven for drying; ②, repeat step 3① 4 to 6 times to obtain HMO@GO / EACC; 4. Preparation of high-priced HMO@GO / EACC: Using HMO@GO / EACC as the positive electrode, platinum sheet as the negative electrode, and 0.5 mol / L H2SO4 solution as the electrolyte, electrolysis was performed at a voltage of 10V to 20V for a period of time to obtain high-valent HMO@GO / EACC; 5. Deposition of PANI on high-priced HMO@GO / EACC: The high-priced HMO@GO / EACC was cleaned with anhydrous ethanol, and the cleaned high-priced HMO@GO / EACC was used as the positive electrode, the platinum sheet was used as the negative electrode, and a mixed solution of aniline and H2SO4 was used as the electrolyte. Deposition was performed at 1V to 2V for a period of time. After the deposition was completed, the carbon cloth was taken out, cleaned, and dried to obtain the high-priced HMO@GO / EACC deposited with polyaniline, that is, the high-priced lithium ion sieve composite graphene oxide loaded carbon cloth deposited with PAIN.
2. The method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth according to claim 1, characterized in that In step 1①, the carbon cloth is washed 2 to 4 times with anhydrous ethanol, acetone and distilled water respectively, and then dried at room temperature; the size of the carbon cloth described in step 1① is (1 cm to 2 cm) × (2 cm to 3 cm).
3. The method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth according to claim 1, characterized in that The HNO3 / H2SO4 acid solution described in step 1② is a mixture of 65% HNO3 by mass and 98% H2SO4 by mass in a volume ratio of 1:1; the constant potential described in step 1② is 4V~6V; the time of electrochemical activation described in step 1② is 10min~20min.
4. The method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth according to claim 1, characterized in that The time of the ultrasonic treatment described in step 2① is 20min to 30min; the mass fraction of the graphene oxide dispersion described in step 2① is 0.5% to 1%.
5. The method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth according to claim 1, characterized in that The mass volume ratio of MnCl2·4H2O, LiOH·H2O, H2O2 solution and deionized water described in step 2② is (3g~5g):(2g~4g):(2mL~4mL):50mL; the mass fraction of the H2O2 solution described in step 2② is 25%~35%; the time of ultrasonic treatment described in step 2② is 1h~2h; the volume ratio of the graphene oxide dispersion described in step 2③ to the mixed solution I is (50mL~100mL):50mL.
6. The method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth according to claim 1, characterized in that The time of the hydrothermal reaction described in step 2④ is 8h to 12h; in step 2④, the reaction product is washed 3 to 5 times with deionized water, then dried at 60°C, and then washed in a 1mol / L HCl solution or a 0.5mol / L sulfuric acid solution for 6h to 10h, filtered, and then dried at 60°C to obtain HMO@GO.
7. The method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth according to claim 1, characterized in that The mass ratio of the mixed powder in the lithium ion sieve slurry described in step 3① to the volume ratio of dimethylacetamide is 1g:(45mL~50mL); the mass ratio of the PVDF powder or polyvinyl pyrrolidone described in step 3① to HMO@GO is (0.1~0.2):(0.8~0.9); the volume ratio of the lithium ion sieve slurry described in step 3① to the surface area ratio of the carbon cloth is (1mL~5mL):(0.8cm 2 ~1cm 2 ); the vacuum drying temperature in step 3① is 60°C to 80°C, and the vacuum drying time is 1h to 2h.
8. The method for preparing a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth according to claim 1, characterized in that The electrolysis time described in step 4 is 0.5h~1h; the high-priced HMO@GO / EACC is cleaned 1~3 times with anhydrous ethanol described in step 5; the mixed solution of aniline and H2SO4 described in step 5 is a mixed solution of aniline, H2SO4 and water, wherein the concentration of aniline is 0.5mol / L~0.15mol / L, and the concentration of H2SO4 is 0.5mol / L~0.15mol / L; the deposition time at 1V~2V in step 5 is 20min~40min; after the deposition in step 5 is completed, the carbon cloth is taken out, cleaned 1~4 times with anhydrous ethanol, and then dried at 60℃~80℃.
9. Application of a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth prepared by the preparation method according to claim 1, characterized in that A PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth is used for electrically controlled lithium extraction.
10. The use of a PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth according to claim 9, characterized in that A PAIN-deposited high-valent lithium ion sieve composite graphene oxide-loaded carbon cloth is used for electrically controlled lithium extraction, which is specifically completed in the following steps: The high-valent lithium ion sieve composite graphene oxide loaded carbon cloth deposited by PAIN is used as a cathode, a platinum sheet is used as an anode, and a lithium-containing solution is used as an electrolyte. Electrolysis is carried out at a voltage of 5V to 7V for 20min to 30min to obtain the high-valent lithium ion sieve composite graphene oxide loaded carbon cloth deposited by PAIN that adsorbs lithium.